1994
DOI: 10.1108/02635579410073495
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Design for Self‐managed Teams

Abstract: Explores the organizational components deemed necessary to the development of heterogeneous self‐managed work teams. Explains the interrelationship between organizational structure and strategies. Describes the organic structure, with emphasis on formalization, socialization, training and empowerment/ decentralization, as the cornerstone of the development of these teams. Outlines strategies for effective use of communication, shared values and trust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…self-renewal (Hong, 1999;Jaw and Liu, 2003;Thibodeaux and Faden, 1994), and knowledge workers and innovative learning (Watkins and Gutzwiller, 1999). This study reinforces this literature and contributes by determining the directionality of the relationship.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…self-renewal (Hong, 1999;Jaw and Liu, 2003;Thibodeaux and Faden, 1994), and knowledge workers and innovative learning (Watkins and Gutzwiller, 1999). This study reinforces this literature and contributes by determining the directionality of the relationship.…”
Section: Discussionmentioning
confidence: 98%
“…In essence, organizations that build trust among employees will also lay the foundation for more effective human and relational intellectual capital management processes. After trust has been established, it makes the gathering and interpreting of information easier (McEvily et al, 2003), and it promotes the acquisition of skills among employees (Thibodeaux and Faden, 1994) and helps to build relationships that involve risk-taking (Mayer et al, 1995), which are all essential for intellectual capital management systems to work properly. Further, Horwitz et al (2003) have suggested that building trust (and other factors) helps employees to turn tacit knowledge into explicit knowledge, thus enabling the organization to build intellectual capital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations